2017
DOI: 10.1016/j.progress.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Contracting out publicness: The private management of the urban public realm and its implications

Abstract: In the UK, there has been a noticeable increase in public space management arrangements based on transfer and contracting-out of managerial responsibilities to organisations outside the public sector, whether in the shape of community or private trusts, tenants organisations, Business Improvement Districts, private companies or voluntary sector organisations. Recent cuts in local authority budgets have accelerated this process. Underpinning it there is an underlying assumption that publicness, however defined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Gardeners experienced a sense of community based on common interests that bring them together (Day, 2006;Delanty, 2010). The investigation found that individual community gardens fit on a scale between a club or community organisation (with formal governance, membership obligations, locked access, and common interests), to a third place (as described by the eight characteristics).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gardeners experienced a sense of community based on common interests that bring them together (Day, 2006;Delanty, 2010). The investigation found that individual community gardens fit on a scale between a club or community organisation (with formal governance, membership obligations, locked access, and common interests), to a third place (as described by the eight characteristics).…”
Section: Resultsmentioning
confidence: 99%
“…As Chitov (2006, p. 454) noted, "bridging social capital is reinforced by the regulars and characters" in community gardens. The Kookaburra Community Garden members exhibited some bonding capital aspects of club rather bridging capital or weak ties than third place-like, with gardeners experiencing a sense of community based on common interests which bring them together (Day, 2006;Delanty, 2010). This element of club-like similarity of interest between members was also in evidence at Frank Street community garden.…”
Section: Growing Social Capital In Community Gardensmentioning
confidence: 99%
“…This includes the public sector, the state working in partnership with the private sector (e.g., business improvement districts around the world), voluntary and third sector organisations, as well as individual volunteers [37]. UK park management is largely carried out by the public sector, with increasing use of external input from contractors [53] and the voluntary involvement of local community groups. The use of contractors is a legacy of the Compulsory Competitive Tendering (CCT) introduced in the UK in 1980 [36], opening up the market to the private, public, and/or third sector, allowing them to bid competitively to deliver parks management [54].…”
Section: Place-keeping: In the Pursuit Of Effective Urban Park Managementioning
confidence: 99%
“…Buizer and Van Herzele found that volunteers don't necessarily represent all the citizens living in an area [58], which is echoed by Mathers et al, who found that green space community groups are largely made up of retired, older white residents [46]. De Magalhães and Trigo pointed out that different governance processes can lead to a reallocation of rights, which prioritises the attributes they (e.g., community group/private sector contractor) have because of their direct involvement in the decision-making [53]. Pillemer et al (2010) highlighted that many older people who volunteer do it for the well-being benefits gained through positive social interaction [51], while others do it to address pressing environmental issues that affect public health [51,59].…”
Section: Place-keeping: In the Pursuit Of Effective Urban Park Managementioning
confidence: 99%
“…However, internal control focuses primarily on compliance while risk management enhances performance . Based on this knowledge, the conceptual framework (Figure 2), outlined a set of variables developed from a wide range of literature relevant to the study (Cofie 2016;Davis 2016;Dementiev 2016;De Magalhães and Trigo 2017;Dong et al 2017;Da Silva Etges et al 2018;Demek et al 2018). We hypothesized the implementation of a commitment to ethics, control environment, segregation of duties, review and information and communication as agents of internal control which could significantly influence and minimize the impact of risk on the performance of public entities.…”
Section: The Conceptual Framework and Hypothetical Assumptionmentioning
confidence: 99%